The Role of Forensic Odontology in Disaster Victim Identification A Case Study Approach (Medical Forum Monthly, 2023)
Objective: To find the role of forensic odontology in disaster victim identification a case study approach.Study Design: Descriptive StudyPlace and Duration of Study: This study was conducted at the Department of Forensic Medicine, Nust School of Health Sciences Islamabad from October 2022 till March 2023.Materials and Methods: Study design to examine the role of forensic odontology in disaster victim identification (DVI). The case study approach allows for an in-depth exploration of a real-world scenario involving mass casualties and the subsequent application of forensic odontology techniques for identification.Results: A total of 25 victims were positively identified using forensic odontology techniques. Identification success rate: 80% of the victims recovered from the disaster were successfully identified through dental comparisons. The application of forensic odontology in disaster victim identification (DVI) yielded substantial outcomes in the examined case study of a commercial airplane crash. A comprehensive collection of ante-mortem dental records was gathered for all passengers and crew members on the ill-fated flight.Conclusion: It is concluded that this case study reinforces the pivotal role of forensic odontology as a cornerstone of disaster victim identification efforts. The successes achieved in this study illuminate the field's potential to provide clarity amidst chaos, healing in the face of tragedy, and ultimately, the restoration of dignity to those who have been lost.